The serum levels of trace metals in Nigerian males with different PSA values (2008)
Prostate cancer (PCa), the primary disease of men over 50 years of age is on the increase worldwide. Most PCa grows slowly from overt clinical disease to the stage that lead to death. The gradual course of PCA development provides opportunity for intervention. Supplement of diet taken by PCa patients may be an effective intervention because certain micronutrients had been implicated in cancer prevention. The present study is designed to determine the levels of trace metals in 80 Nigeria males having different concentrations of serum prostate surface antigen (PSA) using atomic absorption spectrophotometer. The serum levels of PSA were measured with Beckman Coulter Access Immunoassay automated machine. Subjects with PSA values 5-10ng/ml had significantly high serum levels of Zn, Fe, Cd and Mn but significantly low level of Se compared with the controls (PSA 0- 4ng/ml). Subjects with PSA >10ng/ml had significantly low levels of Mn, Mg and Se compared with the controls. Subjects with PSA values 5-10ng/ml had significantly reduced level of Se compared with subjects with PSA >10ng/ml. Only Se was low in all subjects with PSA >4ng/ml, therefore there is a possibility that Se intake may reduce the risk and progression of PCA.